Efecto del gel de extracto etanólico de hojas de piper aduncum en la inflamación inducida en rattus rattus var. norvegicus - Avalos Capristan, César Luis (2016)
Inflammation is a process that occurs tissue with injury, either due to bacteria, trauma, chemicals, heat or any other phenomenon. There are medications used to alleviate inflammatory processes, which must be carefully evaluated, because they produce a variety of side effects. Among the produced side effects include gastrointestinal pathology, and more recently determined an increase in the likelihood of heart attack or stroke. Because the side effects of drugs are difficult to ascertain, traditional medicine continues to be an important option. Piper aduncum is a plant that is attributed medicinal properties, such as wound healing and other antiseptic properties. That is why this work was to determine the effect of gel ethanolic leaf extract Piper aduncum, in inflammation induced in Rattus rattus var. norvegicus. 5 groups (control group, group pattern and 3 groups exposed to gel ethanol extract of leaves of Piper aduncum 1%, 2% and 4%) of 12 specimens and inflammation was induced by injecting 1 mL of carrageenan solution 1 was formed % in the subplantar area of the right hind paw, then applying topical gels prepared with the ethanol extract of leaves of Piper aduncum the problem groups, using a drug (diclofenac gel) in the pattern comparison group. The gel ethanolic extract of Piper aduncum leaves presented antiinflammatory effect, at concentrations of 1%, 2% and 4%, in inflammation induced Rattus rattus var. norvegicus. It was also determined that there is no statistically significant difference between the anti-inflammatory effect of groups and group difference pattern. The antiinflammatory effect could be explained due to the concentration of flavonoids in Piper aduncum leaves.